Migration routes and differences in migration strategies of Whooper Swans between spring and autumn - Ji-Yeon Lee; Hyung-Kyu Nam; Jin-Young Park; Seung-Gu Kang; Nyambayar Batbayar; Dong-Won Kim; Jae-Woong Hwang; Otgonbayar Tsend; Tseveenmyadag Natsagdorj; Jugdernamjil Nergui; Tuvshintugs Sukhbaatar; Wee-Haeng Hur; et al. (Avian Research, 2023)
Long-distance migratory birds travel more rapidly in spring than in autumn, as they face temporal breeding constraints. However, several species travel slower in spring owing to environmental influences, such as food availability and wind conditions. GPS trackers were attached to 17 Whooper Swans (Cygnus cygnus) inhabiting northeastern Mongolia, to determine their migration routes and stopover sites in spring and autumn. Differences between spring and autumn migrations, migration-influencing parameters, and the effect of spring stopover site temperatures were analyzed. Six swans completed perfect tours between their wintering and breeding sites, and these data were used for analysis. Spring migration lasted 57 days, with 49.2 days spent at 3.7 stopover sites. Autumn migration lasted 21.5 days, with 17.5 days spent at 1.0 stopover sites. Thus, the swans traveled more rapidly in autumn than in spring. Migration distance, number of stopovers, migration speed, and straightness were important migration determinants in both spring and autumn. Migration distance, stopover duration, number of stopovers, daily travel speed, travel duration, and migration speed differed significantly between spring and autumn. During spring migration, the temperature at the current stopover sites and that at the future stopover sites displayed significant variations (t ​= ​1585.8, df ​= ​631.6, p ​< ​0.001). These findings are critical for the conservation and management of Whooper Swans and their key habitats in East Asian regions, and the data are anticipated to make a particularly significant contribution toward developing detailed management plans for the conservation of their key habitats.